Business correspondence and communication at work - Shapran, Ludmila; Cherednichenko, Galina; Kunytsia, Lyudmila (My University, 2013)
Textbook is aimed at developing students’ communicative language competences in occupational domain in oral production (speaking) and in written production (writing) activities (business correspondence, job search process, Resume, Cover Letter, contract, business plan, e-mail, fax, memo, etc.). Special attention is also paid to parts and rules of successful oral business communication.
Keywords: бізнес-кореспонденція; business letter; ділове листування; business correspondence; кафедра ділової іноземної мови та міжнародної комунікації